The Role of the Primary Care Physician in the Assessment and Management of Polycystic Ovary Syndrome - Ee, Carolyn (Seminars in Reproductive Medicine, 2023)
Polycystic ovary syndrome (PCOS) is a complex and heterogeneous female endocrine disorder with manifestations that span the hormonal, reproductive, metabolic, and psychological. Primary care physicians (PCPs), also known as family physicians or general practitioners, play a key role in the diagnosis, assessment, and management of PCOS. This article outlines the role of the PCP in the timely and accurate diagnosis, provision of information and education, lifestyle and weight management, and management of key features such as hyperandrogenism, irregular cycles, infertility, emotional well-being, and cardiometabolic risk. PCPs play an essential role as the point of first contact for women and adolescents with or at high risk of PCOS, providers of whole-person care and continuity of care, and coordinators of care within a multidisciplinary team. Optimal management of PCOS requires equitable access to primary care. There is a need for systemic approaches to addressing barriers to provision of quality primary care, such as poor remuneration of longer consultations and low awareness of evidence-based guidelines, to women and adolescents with PCOS.
Keywords: polycystic ovary syndrome; primary care; general practice